Covid-19 Pandemic: The Impact of Product Diversity, Price, Word of Mouth, and Purchase Intention on Impulse Buying Tendency - Nafania Annisa Oktandani; Muhammad Sholahuddin (Jurnal Informatika Ekonomi Bisnis, 2023)
This study examines the influence of product diversity, price, and word of mouth on impulse buying tendencies during the COVID-19 pandemic. The study also explores the role of purchase intention as a mediator in this relationship. The research method employed is both descriptive and causal, with a quantitative approach and primary data collection through interviews, observations, and questionnaires. The sample population consists of consumers of Bluder Cokro Madiun, selected using purposive non-probability sampling. The study employs SEM using PLS to analyze the data and determine the mediating effect. The findings reveal that product diversity has no significant impact on purchase intention, while price and word of mouth have a positive and significant influence. Furthermore, purchase intention positively and significantly affects impulse buying tendencies. This study makes a significant contribution to the knowledge of consumer behavior during the COVID-19 pandemic. The research findings provide insights into how product diversity, price, and word of mouth affect consumers' impulse buying tendencies, and the role of purchase intention as a mediator. This study's findings are valuable for producers and marketers in formulating effective marketing strategies and pricing policies that align with consumer behavior during pandemics. Consumers can also benefit from this study by gaining a better understanding of how their purchase decisions are influenced by product diversity, price, and word of mouth, and their implications for impulse buying. Overall, this study has important practical implications for the marketing industry, particularly during times of crisis.